KEANEKARAGAMAN JENIS KELELAWAR (CHIROPTERA) DALAM KAWASAN HUTAN LINDUNG GUNUNG AMBAWANG KECAMATAN KUBU KABUPATEN KUBU RAYA - Sandriani, Gita; Erianto, .; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2016)
Bats (Chiroptera) is a taxa that has an important function ecologically, such as helping to pollinate flowers, seed dispersal, insect population control and the regeneration of the forest. The aims of this research is to determine the species diversity of bats in Gunung Ambawang protected forest, Kubu Raya regency, West Kalimantan. The method used is catch and release method using mist nest. The result of research obtained that the bats were caught as many as 65 individuals consist of 6 species (Balionycteris maculata, Chironax melanocephalus, Cynopterus minitus, Penthetor lucasii, Hipposideros larvatus, Emballonuridae monticola) belonging to 3 family (Pteropodidae, Hipposideridae, Emballonuridae). Based on the feed, there are 4 species of Bats as frugivorous or fruits eater (Megachirotera) : Balionycteris maculata as many 7 individuals, Chironax melanocephalus 11 individuals, Cynopterus minutus 14 individuals and Penthetor lucasii 7 individuals. Insectivorous or insect eater found 2 species (Microchiroptera) : Hipposideros larvatus as many 14 individuals and Emballonura monticola 12 individuals. Key Word : Diversity, bats, The Mountain of Ambawang Forest Protected.